2015
DOI: 10.4103/2229-5151.164939
|View full text |Cite
|
Sign up to set email alerts
|

Complications of needle thoracostomy: A comprehensive clinical review

Abstract: Needle thoracostomy (NT) is a valuable adjunct in the management of tension pneumothorax (tPTX), a life-threatening condition encountered mainly in trauma and critical care environments. Most commonly, needle thoracostomies are used in the prehospital setting and during acute trauma resuscitation to temporize the affected individuals prior to the placement of definitive tube thoracostomy (TT). Because it is both an invasive and emergent maneuver, NT can be associated with a number of potential complications, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 65 publications
0
14
0
3
Order By: Relevance
“…[26] A serious complication (left ventricular damage) may occur, especially in the lateral approach. [27] Butler et al and Rawlins et al [28] have reported injuries leading to life-threatening bleeding, following NT procedures performed via the 2ICS. We also used 14-G, 8-cm needles in our study, and participants were trained in interventions via the 2ICS, as recommended by the TCCC.…”
Section: Discussionmentioning
confidence: 99%
“…[26] A serious complication (left ventricular damage) may occur, especially in the lateral approach. [27] Butler et al and Rawlins et al [28] have reported injuries leading to life-threatening bleeding, following NT procedures performed via the 2ICS. We also used 14-G, 8-cm needles in our study, and participants were trained in interventions via the 2ICS, as recommended by the TCCC.…”
Section: Discussionmentioning
confidence: 99%
“…Kateter yang tercabut, kusut, tersumbat, atau bila akumulasi udara masuk berlebihan melebihi kemampuan evakuasi kateter bisa menyebabkan terjadinya tension pneumothorax lagi. (6) Permasalahannya adalah untuk memfiksasi needle dengan plester saja tidak kuat (mudah lepas sehingga tidak masuk cavum pleura) sehingga seharusnya dipegang terus hingga terpasang chest tube-WSD yang baru bisa dipasang beberapa jam kemudian. Bertambahnya komplikasi pneumotoraks seperti emfisema subkutis dan gambaran radiologis pneumotoraks yang relatif sama beberapa jam setelah Mini-WSD dicabut, yang seharusnya ada perbaikan gambaran radiologis, bisa dikarenakan kembali meningkatnya tension pneumothorax walaupun sudah dilakukan dekompresi.…”
Section: Pengamatan Lanjutan (Monitoring and Follow-up)unclassified
“…Dengan tindakan needle thoracocentesis di ICS 5, dokter jaga berhasil mengurangi keluhan sesak sementara. Ini sesuai dengan American College of Surgeons (5) bahwa needle dekompresi mengubah tension pneumothorax menjadi simple pneumothorax, dan sesuai dengan Wernick et al (6) bahwa alternatif yang lebih baik sebagai pertimbangan adalah penempatan needle thoracocentesis di linea mid-aksila kelima.…”
Section: Kegagalan/keberhasilan Dibandingkan Pengalaman/fakta Kepustaunclassified
See 1 more Smart Citation
“…Air should be drained from the lungs by performing key emergency interventions. Needle thoracostomy (NT) is a life-saving procedure intended to evacuate tension pneumothorax (TPX) and stabilize the patient until a tube thoracostomy can be inserted (3). The removal of any penetrating foreign body in the chest wall is recommended with video-assisted thoracic surgery (VATS) to control bleeding and damage to the diaphragm and pleura in hemodynamically stable patients; it should not to be performed in the emergency room (4).…”
Section: Introductionmentioning
confidence: 99%